EXISTENCE OF THREE SOLUTIONS FOR NONLOCAL ELLIPTIC SYSTEM OF (p\(_1\) , ... , p\(_n\))-KIRCHHOFF TYPE - Fang, Ming-Lei; Yue, Shan; Li, Chun; Wang, Hao-Xiang (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we establish the existence of at least three solutions to a Dirichlet boundary problem involving the (p1 , ... , pn)-Kirchhoff type systems. Our technical approach is mainly based on the general three critical points theorem obtained by Ricceri.